2012
DOI: 10.1186/ar3806
|View full text |Cite
|
Sign up to set email alerts
|

Risk of end-stage renal disease associated with gout: a nationwide population study

Abstract: IntroductionWe explored the risk of end-stage renal disease (ESRD) among gout patients in a representative cohort in Taiwan.MethodsThe primary database used was the Taiwan National Health Insurance Research Database. Subjects older than 20 years without ESRD, coronary heart disease, or stroke were included in the study. The case definition of gout in the present study was gout diagnosis and medical treatment for gout. An ESRD case was defined by the presence of chronic renal failure necessitating long-term ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 37 publications
5
71
0
7
Order By: Relevance
“…Here, we expanded our previous cohort to include a non-gout population, with and without CKD, for comparison. An important assumption was that patients with an established diagnosis of gout were more likely to have chronic urate-related renal damage, as supported by recent large-scale epidemiological studies [18, 19]. Leakage of UMOD has been known to cause inflammation of renal tissue, and a previous study [7] reported that damage to the TAL of a nephron and cells distal to the TAL results in leakage of UMOD into the interstitium, and subsequent inflammation.…”
Section: Introductionmentioning
confidence: 86%
“…Here, we expanded our previous cohort to include a non-gout population, with and without CKD, for comparison. An important assumption was that patients with an established diagnosis of gout were more likely to have chronic urate-related renal damage, as supported by recent large-scale epidemiological studies [18, 19]. Leakage of UMOD has been known to cause inflammation of renal tissue, and a previous study [7] reported that damage to the TAL of a nephron and cells distal to the TAL results in leakage of UMOD into the interstitium, and subsequent inflammation.…”
Section: Introductionmentioning
confidence: 86%
“…The global epidemiology of gout data showed that the worldwide prevalence of gout ranges from 0.1% to approximately 10%, and developed countries tend to have a higher burden of gout than developing countries, while gout incidence of men is higher than women by 2-6 fold [2]. Most frequently, gout causes recurrent attacks of acute arthritis and tophi depositions, and other chronic diseases, such as common complications of renal [3], metabolic syndrome [4], hypertension and cardiovascular diseases [5,6]. Therefore, the treatment of gout has become a serious problem to solve.…”
Section: Introductionmentioning
confidence: 98%
“…Both gout and HUA have been associated with a number of pathological conditions such as metabolic syndrome, obesity, hypertension, stroke, cardiovascular diseases, and renal diseases [3][4][5][6]. However, the effects of gout/HUA on oral health remain unknown.…”
Section: Original Papermentioning
confidence: 99%